Associations of NSAID and paracetamol use with risk of primary liver cancer in the Clinical Practice Research Datalink. (August 2016) - Yang, Baiyu; Petrick, Jessica L.; Chen, Jie; Hagberg, Katrina Wilcox; Sahasrabuddhe, Vikrant V.; Graubard, Barry I.; Jick, Susan; McGlynn, Katherine A.
Highlights: Prescription NSAID use is not associated with risk of primary liver cancer. Ever-use of paracetamol is associated with slightly higher liver cancer risk. Paracetamol—liver cancer association is stronger among leaner individuals. Abstract: Liver cancer incidence has been rising rapidly in Western countries. Nonsteroidal anti-inflammatory drugs (NSAIDs) and paracetamol are widely-used analgesics that may modulate the risk of liver cancer, but population-based evidence is limited. We conducted a case-control study (1195 primary liver cancer cases and 4640 matched controls) within the United Kingdom's Clinical Practice Research Datalink to examine the association between the use of prescription NSAIDs and paracetamol and development of liver cancer. Multivariable-adjusted odds ratios (aORs) and 95% confidence intervals (CIs) were estimated using conditional logistic regression. Overall, ever-use of NSAIDs was not associated with risk of liver cancer (aOR = 1.05, 95% CI = 0.88–1.24), regardless of recency and intensity of use. Use of paracetamol was associated with a slightly increased risk of liver cancer (aOR = 1.18, 95% CI = 1.00–1.39), particularly among individuals with body mass index < 25 kg/m 2 (aOR = 1.56, 95% CI = 1.17–2.09). Our results suggest that NSAID use was not associated with liver cancer risk in this population. Ever-use of paracetamol may be associated with slightly higher liver cancer risk, but results should be interpreted cautiously due to methodological limitations. Given that paracetamol is a widely-used analgesic, further examination of its relationship with liver cancer is warranted.